Palynomorph Biozonation of the Malawa Formation, Barru Region, South Sulawesi - Zulfiah Zulfiah; Nurhikmah Supardi (Jambura Geoscience Review, 2023)
This study's subject is the Padanglampe traverse in Tanete Riaja, Barru Regency, at coordinates 040 30' 25.26" South Latitude and 1190 41' 43.43" East Longitude. Padanglampe sedimentary deposits of The Malawa Formation were the subject of this study. This study aims to establish the Malawa formation's age based on the presence of palynomorph fossils. Vertical measurement with a track thickness of approximately 10.5 meters was used for field investigation. The sediment's grain size helps to separate the two sections of the Padanglampe traverse. The top layer comprises coal layers and moderately fine- to medium-grained sediments. Coarse-grained sandstone makes up the lowest layer. At any spacing of 25 cm from the measurement of the stratigraphic cross-section, rock sampling was methodically done, yielding 45 lithology samples. A polarizing microscope with a 40x magnification was used to prepare and examine the material. Only 36 samples were used in the subsequent analysis, with nine barren samples. The palynomorph composition of each sample was determined quantitatively and displayed in a palynological diagram using the CONISS technique to measure the data based on life types. Based on the outcomes of observations, 64 pollen taxa and 17 spore taxa were identified. The Moraceae, Palmaepollenites, Spinizonocolpites echinatus, Pandanidites, Proxapertites operculatus, Laevigatosporites, Acrostichum, and Anthocerisporites are those with the greatest abundance. It is split into six informal palynomorph assemblage zones, labeled as zone I - zone IV using cluster analysis. Based on the palynomorph data, the age of the Malawa Formation is Middle Eocene – Upper Eocene.